2004
DOI: 10.1002/elps.200305733
|View full text |Cite
|
Sign up to set email alerts
|

Different binding thermodynamics of Ni2+, Cu2+, and Zn2+ to bacitracin A1 determined by capillary electrophoresis

Abstract: Thermodynamics of the binding of Ni(2+), Cu(2+) and Zn(2+) to bacitracin A(1) was studied by capillary electrophoresis measuring the peptide effective mobility at different pH in the presence of increasing concentration of the three ligands. The affinity follows the order Ni(2+) > Cu(2+) > Zn(2+), with association constant values of (2.3 +/- 0.1)x10(4), (4.9 +/- 0.2)x10(3), and (1.5 +/- 0.1)x10(3) M(-1), respectively. The only model able to rationalize mobility data implies that metal ion binds to the P(0) pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…In the same experimental arrangement, CE was used to determine the stability constants and kinetic parameters for the complexes of lanthanide ions with 1,4,7,10-tetraazacyclodecane-N',N'',N'''-tetraacetic acid [267]. Similar CE studies have been reported on complex formation between metal ions and bioligands (such as polypeptides [268][269][270] or metal-containing proteins [271]) and on elucidating the mechanism of perrhenate reduction [272], interaction of lower oxidation states of Re with 1-hydroxyethylidenediphosphonic acid [210], and the redox reaction between Fe(II) and desferrioxamine B [273].…”
Section: Chemical Equilibrium and Kinetic Studiesmentioning
confidence: 94%
“…In the same experimental arrangement, CE was used to determine the stability constants and kinetic parameters for the complexes of lanthanide ions with 1,4,7,10-tetraazacyclodecane-N',N'',N'''-tetraacetic acid [267]. Similar CE studies have been reported on complex formation between metal ions and bioligands (such as polypeptides [268][269][270] or metal-containing proteins [271]) and on elucidating the mechanism of perrhenate reduction [272], interaction of lower oxidation states of Re with 1-hydroxyethylidenediphosphonic acid [210], and the redox reaction between Fe(II) and desferrioxamine B [273].…”
Section: Chemical Equilibrium and Kinetic Studiesmentioning
confidence: 94%
“…Castagnola et al studied the binding of metal ions (Ni 2+ , Cu 2+ , and Zn 2+ ) to the dodecapeptide bacitracin by ACE [39,40]. In these studies the peptide effective mobility was measured at varying pH in the presence of increasing concentration of metal ion.…”
Section: Metal-small Moleculementioning
confidence: 98%
“…Through calculating the binding constants between aromatic phosphonic acids and ammonium and potassium cations, the thermodynamic selectivity of complexation was assessed and compared with the data of molecular mechanics [237]. The association constants for the binding of Ni(II), Cu(II), and Zn(II) toward a polypeptide was studied by measuring its effective mobility at different pH and metal concentrations [238]. Transition metal ions were found to play a negative role on DNA genotyping, causing the CE peaks of DNA samples to be poorly resolved [239].…”
Section: Study Of Chemical Reactionsmentioning
confidence: 99%